Scapular fracture in a racehorse with a long career of uninterrupted intense exercise - CO, Schild; J, Asin; JA, Jeff A. Blea; S, Stover; FA, Uzal (Brazilian Journal of Veterinary Pathology, 2023)
A thee-year-old Thoroughbred gelding racehorse completed 12 races in 13 months at high-level competition. The horse had a catastrophic injury on the left front leg during high-speed five-furlong workout on a dirt racetrack in California. It was the second official timed high-speed workout withing 27 days of his last race. The horse pulled up during workout, could not bear weight on the left forelimb, had the shoulder region swollen and elicited pain in the shoulder joint upon extension and adduction.